100% Orange Juice Consumption is Associated with Socioeconomic Status, Improved Nutrient Adequacy, and Higher Bioactive Compounds Intake: Results from Brazilian National Dietary Survey 2017-2018 - Carnauba, Renata A; Sarti, Flavia M; Hassimotto, Neuza M A; Lajolo, Franco M (Journal of the American Nutrition Association, 2024)
The consumption of 100% orange juice (OJ) has been associated with nutrient adequacy and better diet quality. To date, there are few analyses exploring 100% OJ consumption patterns across populations, with no data from Brazil. We aimed to explore the associations between 100% OJ consumption, sociodemographic factors, and nutrient intake in a representative sample of the Brazilian general population aged 10 years or older. Data were obtained from the National Dietary Survey 2017-2018, a cross-sectional study including data on individual food intake of 46,164 subjects aged ≥10 years collected using two 24-h dietary recalls. 100% OJ was consumed by 11% of the population, with a mean intake of 43.0 ml/d. Males were more frequent consumers compared to females, and the percentage of consumers increased with education and income. 100% OJ consumption was associated with higher intakes of energy, vitamin C, folate, calcium, magnesium, potassium, polyphenols, and carotenoids. There is no significant difference in fiber intake between consumers and non-consumers. 100% OJ consumers had a higher percentage of the population meeting the Estimated Average Requirement for vitamin A, vitamin C, vitamin D, folate, calcium, and magnesium. Our results suggest that 100% OJ could be a component of a healthy diet, helping individuals to achieve nutrient recommendations.